2011
DOI: 10.1128/aem.05675-11
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Cryptosporidium parvum Oocysts, Escherichia coli, and a Salmonella enterica Serovar Typhimurium Bacteriophage through Intact Soil Cores following Surface Application and Injection of Slurry

Abstract: Increasing amounts of livestock manure are being applied to agricultural soil, but it is unknown to what extent this may be associated with contamination of aquatic recipients and groundwater if microorganisms are transported through the soil under natural weather conditions. The objective of this study was therefore to evaluate how injection and surface application of pig slurry on intact sandy clay loam soil cores influenced the leaching of Salmonella enterica serovar Typhimurium bacteriophage 28B, Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…Retention of Escherichia coli similar to that found for oocysts in our study was seen for E. coli when using the same soil columns (1). Forslund et al (15) found that intact soil cores injected with raw pig slurry spiked with C. parvum leached 10 times more oocysts than did soil cores applied with slurry on the surface after 148 days of study under natural climate conditions. However, the amount of oocysts retained in the soil was not determined (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retention of Escherichia coli similar to that found for oocysts in our study was seen for E. coli when using the same soil columns (1). Forslund et al (15) found that intact soil cores injected with raw pig slurry spiked with C. parvum leached 10 times more oocysts than did soil cores applied with slurry on the surface after 148 days of study under natural climate conditions. However, the amount of oocysts retained in the soil was not determined (15).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the transport of Cryptosporidium oocysts through soil (4,8,9,15,25,32), but none of these studies evaluated the leaching of oocysts following application of separated liquid slurry containing oocysts. In our study, soil columns with injected liquid slurry released more oocysts over the 4-week study period than did soil columns with added raw slurry regardless of the application method, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil physicochemical properties, e.g., mineralogy, natural organic matter content, and pH, critically affect the parasite-particle interactions and the mobilization behavior of Cryptosporidium oocysts (43,52,79,81,82). Spatial dissemination of excreted parasites depends also on local hydrodynamic forces and occurs mainly by leaching, typically following heavy rainfalls, leading to the possible entry of the parasites into water (39,84). It has been shown that wetlands with established vegetation may efficiently retain parasites, while degraded habitats promote pathogen pollution of waters, with great impact on humans and animals (100,106).…”
Section: Surface Interactions Drive the Transport And Survival Of Parmentioning
confidence: 99%
“…Although contamination by these organisms is of concern given the risk associated with the transmission of infectious and parasitic diseases through the food chain (MACIOROWSKIA et al, 2007;SILVA et al, 2005), other studies show that enteric organisms either do not survive or have a high rate of decline in fertilized soil (GAGLIARDI; KARNS, 2002;GARCÍA-ORENES et al, 2007;TALLON et al, 2007;ZIEMER et al, 2010). The discrepancies in the literature about enteropathogenic bacterial contamination of soil are related to the many different factors that affect the survivability of enteric organisms in the soil, including the type of organic fertilizer; fertilized crop, management and dosage; the use of mitigation practices; and environmental factors such as soil type, pH, humidity and temperature (MACIOROWSKIA et al, 2004;FORSLUND et al, 2011). However, the survival of pathogenic organisms in latosols fertilized with poultry manure has not been studied in Brazilian soils and climate conditions, and there are only a few reports from other countries (McMURRY et al, 1998).…”
Section: Introductionmentioning
confidence: 99%